The second epistle of Paul to the Corinthians an introduction and commentary - Tasker, R.V.G. (London, UK Tyndale, 1958)
Includes bibliographical references.
1969 reprint
Keywords: Bible. N.T. Corinthians, 2nd -- commentaries